Clinical insomnia among elderly primary care attenders in Wuhan, China: A multicenter cross-sectional epidemiological study - Zhong, Bao-Liang; Li, Hong-Jie; Xu, Yan-Min; Jiang, Xue-Feng (Frontiers in Public Health, 2022)
Background and objectives Integrating sleep health into primary care is a promising approach to narrow the treatment gap for insomnia in older adults but data regarding the epidemiological characteristics of insomnia among elderly primary care attenders (EPCAs) are very limited. This study examined the prevalence and correlates of clinical insomnia among Chinese EPCAs. Methods By using two-stage consecutive sampling method, a total of 757 EPCAs were recruited from seven urban and six rural primary care centers in Wuhan, China. The Insomnia Severity Index (ISI) and the Geriatric Depression Scale (15 item version) were administered to assess insomnia severity and depressive symptoms, respectively. Results The two-week prevalence of clinical insomnia (ISI score ≥ 15) was 28.9%. Significant correlates of clinical insomnia were: female sex (vs. male, OR = 2.13, P < 0.001), fair and poor family relationship (vs. good, OR = 1.59, P = 0.028), hypertension (OR = 1.67, P = 0.004), heart disease (OR = 1.73, P = 0.048), arthritis (OR = 2.72, P = 0.001), and depressive symptoms (OR = 4.53, P < 0.001). Conclusion The high prevalence of clinical insomnia among Chinese EPCAs suggests a high level of sleep health need in older patients in China's primary care settings. Considering the many negative outcomes associated with insomnia, it is necessary to integrate sleep health into primary care in China.